(untitled) (Journal of Engineering, 2007)
The present paper presents an approach to optimize tooth contact analysis (TCA) of spiral bevel gear drivin by controlling the machine-tool settings that directly affects the shape of tooth and behavior of meshing and contact for mating gears. The proposed settings provide a pre-designed parabolic function of transmission errors and the desired location and orientation of the bearing contact. The main goal of detecting the pre-designed parabolic function of transmission errors is to reduce the gear noise which can be done by absorbing the linear function of transmission errors that are caused by gear misalignment. The model is generated with means of CAD software package and solid works program, the basic input design data imported by Gleason works standards.